2021
DOI: 10.1038/s41598-021-92814-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum IgG4 levels at diagnosis can predict unfavorable outcomes of untreated patients with IgG4-related disease

Abstract: The outcomes of patients with immunoglobulin G4 (IgG4)-related disease (IgG4-RD) who are not treated are unclear. This study aimed to clarify these outcomes and identify the factors related to them. We retrospectively evaluated various clinical features including laboratory data and involved organs at diagnosis in 107 patients with IgG4-RD, who were followed up for more than 6 months, at a single center in Japan. We compared the clinical features of the 27 untreated patients with those of the 80 patients treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…Previous meta-analysis study reported a similar rate of efficacy of first-line therapies (96%) and relapse (33%). [9,24] In the present study, the occurrence of relapse was not related to laboratory findings at baseline including IgG4, IgG, FLC, FLC ratio, HLC, and HLC ratio. The role of IgG4 as a marker of disease relapse has shown inconsistent results.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Previous meta-analysis study reported a similar rate of efficacy of first-line therapies (96%) and relapse (33%). [9,24] In the present study, the occurrence of relapse was not related to laboratory findings at baseline including IgG4, IgG, FLC, FLC ratio, HLC, and HLC ratio. The role of IgG4 as a marker of disease relapse has shown inconsistent results.…”
Section: Discussioncontrasting
confidence: 43%
“…[24] However, Mizushima et al reported that baseline serum IgG4 concentration can be predictive of unfavorable outcomes in untreated patients. [24] Also, Culver et al, in a prospective cohort, have reported that baseline serum IgG4 concentration was higher in patients who relapsed after therapy than patients who did not relapse (median 505 mg/dL vs 195 mg/dL). [19] This inconsistency among reports may be due to the different size of the patient population, the design of the study, and different treatment outcomes, and the role of the initial IgG4 level as a marker of disease relapse should be resolved in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] Another report presented that 1 of 27 untreated patients with IgG4-RD obtained spontaneous improvement of the lacrimal gland lesion; however, the detailed clinical findings were not presented. [8] The mechanisms of spontaneous regression remain unclear. A previous report postulated that decreased absolute amount of IgG4-positive plasmacytes after biopsy induces an abnormal immune response.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] In contrast, although rare, IgG4-related dacryoadenitis is spontaneously resolved without steroids. [7,8] There have been only a few reported cases of spontaneous regression of IgG4related dacryoadenitis. [7,8] Here, we report an additional case of IgG4-related dacryoadenitis and multiple organ involvement with spontaneous resolution.…”
Section: Introductionmentioning
confidence: 99%